Adaptive Coping Strategies of Indonesian Migrant Children in Malaysia: A Study on Counseling Approaches at PKBM PNF KBRI Kuala Lumpur - Achmad Chairudin; Bambang Subahri (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
Indonesian migrant children in Malaysia face various psychosocial challenges influenced by limited access to education, family economic conditions, administrative status, and minimal parental support. Various studies have examined the mental health and resilience of migrant children, but research on adaptive coping strategies reinforced thru guidance and counseling services in non-formal educational institutions is still relatively limited. This study aims to analyze the adaptive coping strategies of Indonesian migrant children and examine the contribution of counseling approaches in strengthening coping abilities at PKBM PNF KBRI Kuala Lumpur. The research uses a qualitative approach with a case study design. Participants were purposively selected, including the head of PKBM, teachers, students, and parents. Data were collected thru in-depth interviews, observations, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña with credibility tests thru source triangulation, technique triangulation, and member checks. The research results show that migrant children face pressures stemming from their family's economic limitations, low parental supervision, and difficulties in academic and social adaptation. To cope with these conditions, students develop problem-focused coping, emotion-focused coping, and social support coping strategies, with social support from teachers and peers being the most dominant strategy. The counseling approach thru personal guidance, character building, and emotional support has proven to strengthen students' problem-solving abilities, emotional regulation, self-confidence, and adjustment. These findings affirm that guidance and counseling services in non-formal education play a strategic role in strengthening the adaptive coping of migrant children while also providing conceptual and practical contributions to the development of psychosocial services for Indonesian migrant children abroad.